1996
DOI: 10.1074/jbc.271.25.14734
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Spectroscopic Characterization of the Hydrogenosomal [2Fe-2S] Ferredoxin from the Protozoan

Abstract: The heterologous expression and spectroscopic characterization of the [2Fe-2S] ferredoxin from the sexually transmitted human parasite Trichomonas vaginalis is described. Using oligonucleotide primers based on the deduced DNA sequence, the gene encoding the ferredoxin was amplified by polymerase chain reaction and cloned into a T7 RNA polymerase expression vector. Expression of the gene in Escherichia coli host HMS174(DE3) resulted in the high level production of the protein with the correctly assembled iron-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 29 publications
3
12
0
Order By: Relevance
“…It has previously been observed that FdI migrates abnormally on SDS-12% PAGE as if its molecular weight were ϳ24,000 rather than 12,000 (57). Such anomalous behavior on SDS-PAGE has previously been re-ported for other small and highly charged proteins (the isoelectric point of FdI calculated from amino acid sequence is 4.03) (58). The similar purification properties and electrophoretic behaviors of FdIV and FdI suggested that they were likely to have similar charges and molecular weights.…”
Section: Resultsmentioning
confidence: 80%
“…It has previously been observed that FdI migrates abnormally on SDS-12% PAGE as if its molecular weight were ϳ24,000 rather than 12,000 (57). Such anomalous behavior on SDS-PAGE has previously been re-ported for other small and highly charged proteins (the isoelectric point of FdI calculated from amino acid sequence is 4.03) (58). The similar purification properties and electrophoretic behaviors of FdIV and FdI suggested that they were likely to have similar charges and molecular weights.…”
Section: Resultsmentioning
confidence: 80%
“…The hydrogenosomal [2Fe-2S]-ferredoxin of Trichomonas has been characterized (164,228,540); it is one of the few Trichomonas proteins that has been studied at the crystal structure level (92). Trichomonad hydrogenosomes contain components derived from complex I of the mitochondrial respiratory chain that help to maintain redox balance by reoxidizing NADH from the malic enzyme reaction (209).…”
Section: Fig 11mentioning
confidence: 99%
“…3A). As a control, Western analysis was performed using antisera against ferredoxin, a protein with three cysteine residues that coordinate iron (34).…”
Section: Isolation and Characterization Of Hmp35 A Hydrogenosomalmentioning
confidence: 99%